A night in the life of a migrant street artist: In conversation with visual artist Shp. Issue 1 (1st April 2022) - Pardue, Derek; Santos, Eduardo
The following text is a transcription and translation from a conversation with Eduardo Santos, a Brazilian tagger and street artist who currently lives in Lisbon, Portugal. Santos, more widely known as Shp ('sheep'), member of the group Pregos (literally translated as 'nails'), responded to questions about identity, life philosophy and art through a series of WhatsApp audios. In addition, Shp and Xiên, another Brazilian migrant, provide a voice-over for a ten-minute video that shows a 'night in the life' of a pixador, the name given in Brazilian Portuguese to a street artist who practises the Brazilian variant that mixes elements of tagging and graffiti. Topics broached include: a comparison between pixo and Brazilian funk, marginalized arts, the street, the origins of pixo in Lisbon, respect and the presence of Brazil in the tuga (Portugal). English subtitles were done by Mariana Gil, a Brazilian photographer and migrant living in Aarhus, Denmark (video link: https://www.instagram.com/tv/CQYue_MnUuk/?utm_medium=copy_link ).